TAKARAN DAN KRITERIA PASTA GIGI YANG TEPAT UNTUK DIGUNAKAN PADA ANAK USIA DINI (APROPRIATE AMOUNT AND CRETERIA OF TOOTH PASTE USED FOR EARLY-AGED CHILDREN) - Sukanto Sukanto (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2012)
ABSTRACT Dental caries in early-aged children still occurs frequently. One of its causes is the less dental hygiene, children are still incapable to maintain their oral and dental health independently. One of material to help in cleaning teeth is toothpaste. The choice of this material should be appropriate in order to obtain optimum dental hygiene and not result in negative impacts. The products available in the market generally claim themselves as the best one by showing their excellences e.g. brand, interesting package, low price, and quality. Those necessitate the customer especially parents to be selective in choosing appropriate toothpaste for their children. The choose of toothpaste should consider some aspects including the composition, development of child age, criteria required based on the age, product variant, and side effect. In conclusion, the criteria of the chosen toothpaste: should be base on safe package and interesting, colours, scent and taste liked by children.